Impact of ISP, BPR, and customization on ERP performance in manufacturing SMEs of Korea - HONG, Soon-Goo (Institutional Knowledge at Singapore Management University, 2016)
Purpose: This paper aims to assess how enterprise resource planning (ERP) performance of Korean small and medium enterprises in manufacturing differs according to different levels of business process reengineering (BPR), information strategic planning (ISP) and ERP customization. Design/methodology/approach: A questionnaire survey was carried out in this research. Responses from 96 small and medium manufacturing companies that have adopted ERP systems were analyzed. Findings: The results of this study suggest that ISP and BPR implementation are positively correlated to ERP performance. Originality/value: While consulting and customization costs have positive impacts on ERP performance, the level of customization does not influence performance. As one of the pioneering studies that investigate the impact of BPR, ISP and ERP customization on small and medium manufacturing companies, this research contributes to both theory and practice.